2020
DOI: 10.1186/s12957-020-1806-2
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 polymorphisms and predisposition to digestive system malignancies: a meta-analysis of 31 published studies

Abstract: Background The results of genetic association studies regarding cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) polymorphisms and digestive system malignancies were controversial. The authors designed this meta-analysis to more precisely estimate relationships between CTLA-4 polymorphisms and digestive system malignancies by pooling the results of related studies. Methods The authors searched PubMed, Embase, Web of Science, and CNKI for eligible studies. Thirty-one eligible studies were pooled analyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
(19 reference statements)
1
15
1
Order By: Relevance
“…Due to discrepancies observed in aforementioned publications future well designed studies are needed to resolve ambiguities between published results. For CTLA-4c.-1722T>C , CTLA-4c.-1661A>G , CTLA-4c.-319C>T , and CTLA-4CT60G>A , there was no evidence of associations with CRC risk ( 94 , 114 ).…”
Section: Cytotoxic T Lymphocyte-associated Antigen-4mentioning
confidence: 88%
See 4 more Smart Citations
“…Due to discrepancies observed in aforementioned publications future well designed studies are needed to resolve ambiguities between published results. For CTLA-4c.-1722T>C , CTLA-4c.-1661A>G , CTLA-4c.-319C>T , and CTLA-4CT60G>A , there was no evidence of associations with CRC risk ( 94 , 114 ).…”
Section: Cytotoxic T Lymphocyte-associated Antigen-4mentioning
confidence: 88%
“…This meta-analysis showed that in the Chinese population the CTLA-4c.49 A/A genotype increased the risk of HCC of about 1.5-fold. On the other hand, the most recent meta-analysis by Li et al ( 94 ) [analyzing data included in work by Wang et al ( 101 ), except one study published in Chinese language ( 104 ), and data from two additional studies ( 105 , 106 )], did not confirm previous observations and suggested a lack of association between the CTLA-4c.49A>G and HCC risk.…”
Section: Cytotoxic T Lymphocyte-associated Antigen-4mentioning
confidence: 89%
See 3 more Smart Citations